Pseudo aneurysm of uterine artery and cesarean scar dehiscence causing secondary post-partum haemorrhage managed by uterine artery embolisation: a case report - Singh, Kalpana; Bharati, Geetam; Kumari, Smita; Tripathy, Nishant (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Uterine artery pseudo aneurysm is rare but potentially life threatening complication of cesarean section and may present with severe secondary postpartum haemorrhage. Here we report a case of secondary postpartum haemorrhage due to pseudo aneurysm of left uterine artery and cesarean scar dehiscence in 27 yrs old women which was managed successfully with uterine artery embolisation at IGIMS, Patna. These 27 yrs old young women presented with severe secondary PPH forty days following cesarean section. Ultrasound and CT scan abdomen was done which showed full thickness defect in the lower segment of uterus and focal enhancement in the early arterial and late venous phase in left parametrium. Pseudo aneurysm being rare was not suspected and patient underwent laparotomy. Twenty two days after surgery patient again had heavy bout of vaginal bleeding. Doppler Ultrasound was done which showed large pseudo aneurysm of left uterine artery which was then managed successfully with uterine artery embolisation. Although rare but pseudo aneurysm of uterine artery should be suspected in case of secondary PPH where other common causes has been excluded. Angiographic embolisation of uterine artery is safe and effective method for treating secondary PPH due to pseudo aneurysm of uterine artery in haemodynamically stable patient. Therefore, in modern obstetrics hysterectomy should be the last option to treat postpartum haemorrhage.